Analysis of the association between reading and writing postures and comorbidity of myopia and scoliosis in junior middle school students - Wang, Yanjiao; Yang, Dongling; Zhang, Fengyun; Qi, Wenjuan; Lu, Qiuying; Wu, Haotian; Luo, Chunyan (Frontiers in Pediatrics, 2025)
ObjectiveGiven the emerging co-prevalence of myopia and scoliosis as significant public health challenges among Chinese adolescents, and considering sustained poor reading/writing postures as a potential shared risk factor contributing to onset, progression, and comorbidity, this study aimed to investigate the epidemiological association between myopia and scoliosis, specifically evaluate the synergistic effects of poor reading/writing postures on these conditions, and establish evidence-based strategies for coordinated prevention of comorbid orthopaedic-ophthalmic disorders.MethodsThe study population comprised adolescents aged 11–15 years enrolled in junior middle schools across Shanghai. All participants underwent comprehensive ocular examinations, standardized scoliosis screening, and completed structured questionnaires assessing demographic and behavioral risk factors.ResultsThis study included 9,583 middle school students (mean age 12.59 ± 1.17 years). Overall myopia prevalence was 77.6%, while the scoliosis prevalence was 1.7%. Notably, 87.2% of the scoliosis cohort had concurrent myopia, compared to 77.4% in the non-scoliosis group. The dual-disease comorbidity rate was 1.5% (males: 1.0%; females: 2.1%). Multivariable logistic regression analysis revealed that poor reading/writing postures (OR = 1.17, 95% CI: 1.02–1.34) and scoliosis screening positivity (OR = 1.74, 95% CI: 1.09–2.76) were significantly associated with increased myopia risk. Conversely, myopia demonstrated a bidirectional association with elevated scoliosis susceptibility (OR = 1.73, 95% CI: 1.09–2.75). For dual-disease cases, advancing school grade and female sex were positively correlated with comorbidity. Systematic implementation of postural breaks after 30-minute near-work intervals (OR = 0.65, 95% CI: 0.46–0.91) and teacher-mediated posture monitoring (OR = 0.66, 95% CI: 0.45–0.97) significantly reduced comorbidity risks compared to sporadic practice.ConclusionsA significant bidirectional association exists between adolescent myopia and scoliosis, with non-ergonomic reading/writing postures identified as a shared modifiable risk factor. Education functional departments should implement evidence-based interventions including postural ergonomics education, routine vision and spinal screening programs, and structured postural breaks after near-work intervals to mitigate dual-disease burdens in adolescents.